2020
DOI: 10.1016/j.omtn.2020.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of Long Non-coding RNA and Messenger RNA in Human Traumatic Brain Injury

Abstract: Long non-coding RNAs (lncRNAs) and messenger RNAs (mRNAs) play an important role in central nervous diseases; however, the exact expression and co-expressed profiles in human traumatic brain injury (TBI) are still unknown. Therefore, we investigated whole blood in 12 patients with TBI and 4 healthy controls to observe expression characteristics with different severity. We identified 3,035 lncRNAs and 1,204 mRNAs differentially expressed in the severe TBI group, 2,362 lncRNAs and 656 mRNAs in the moderate group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Moreover, 2.5% of patients with moderate to severe TBI were predicted to have an onset of acute ischemic stroke [ 34 ]. Recently, the lncRNA profiles in TBI were investigated in the mouse cortex [ 35 ] and in whole blood samples derived from TBI patients, leading to the identification of 10 significantly altered expressed lncRNAs [ 36 ]. Meanwhile, following TBI injury, various regulatory lncRNAs, such as metastasis-associated lung adenocarcinoma transcript 1 ( MALAT1 ), could be used as an approach or delaying secondary injury progression.…”
Section: Strokementioning
confidence: 99%
“…Moreover, 2.5% of patients with moderate to severe TBI were predicted to have an onset of acute ischemic stroke [ 34 ]. Recently, the lncRNA profiles in TBI were investigated in the mouse cortex [ 35 ] and in whole blood samples derived from TBI patients, leading to the identification of 10 significantly altered expressed lncRNAs [ 36 ]. Meanwhile, following TBI injury, various regulatory lncRNAs, such as metastasis-associated lung adenocarcinoma transcript 1 ( MALAT1 ), could be used as an approach or delaying secondary injury progression.…”
Section: Strokementioning
confidence: 99%
“…Generally, long non-coding RNAs (lncRNAs) are non-coding RNA (ncRNA) transcripts greater than 200 nucleotides (nt) in length. These non-coding sequences were identified in the 1970s ( Iyer et al, 2015 ; Ren et al, 2020 ). At present, the general understanding of evolutionary biology states that lncRNAs have no biological function and are, therefore, “junk DNA” ( Chen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…lncRNAs are also involved in various pathophysiological mechanisms of central nervous system (CNS) diseases, and targeting these lncRNAs can treat most CNS diseases (Ang et al, 2020;Kahaei et al, 2020;Tian et al, 2020), such as Alzheimer's disease (Zhang et al, 2018), and ischemic stroke (Zhang et al, 2021). Furthermore, lncRNAs have specific expression profiles in brain tissue and can be used as potential independent prognostic molecular markers (Kadakkuzha et al, 2015;Ren et al, 2020). Several recent studies demonstrated the importance of lncRNAs in TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (2019) observed expression characteristics of lncRNAs and mRNAs in human TBI tissues in the acute stage. Ren et al (2020) investigated the expression profiles of lncRNAs and mRNAs in blood from TBI patients. Abundant evidence suggests that various lncRNAs are aberrantly expressed in mouse TBI tissues and can improve TBI by inhibiting the inflammatory response of microglia in the acute phase (Wang et al, 2017;Zhong et al, 2017;Patel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%